Pedestrian Planning in City Centers: a Study of Guimarães and Braga - Rahaman, Khan Rubayet; Lourenço, Júlia (TeMA - Journal of Land Use, Mobility and Environment, 2010)
People are walking in cities for different reasons. Some walkers walk for going to work, some are walking for shopping and some are for leisure during day and night hours. Medium sized cities like Braga and Guimarães in Portugal are depending on car for even shorter trips up to 2 kilometers. However, the walkways are allowing people to walk in convenient and safe way including late night environment. The pedestrians feel troublesome to walk on the footpaths because of illegal parking and discontinuation of walkways. Municipality transport plans and master plans do not incorporate pedestrians as a major component. But this egress mode of transportation is very important in medium sized city centers like Guimarães and Braga for the people to enjoy city centers’ activities. This paper focuses on the types of walkers who use the walkways on a regular basis. Usually, people are feeling comfortable to walk when they go to clubs and bars in a group in these small cities especially after work. This paper again tries to focus the varieties of problems on walkways and to present policies that can improve the situation. Municipal master plan and transportation plan have been studied carefully to see the provisions of pedestrian planning options. Field surveys have been conducted both in form of questionnaire and observation during the end of 2009 and results show different patterns of pedestrian behavior as well as evidence that people get different experiences with problems while walking on the walkways in both surveyed towns. Considering the issues of sustainable mobility, this paper also tries to suggest policies to motivate more people to walk especially in the medium-sized cities of Portugal.